(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the construction, relevance, effectiveness, and ideal reconstruction of criminal sanctions for cybercrime from the perspective of Law Number 1 of 2023 concerning the Criminal Code. The method used is a normative juridical approach supported by limited empirical data through literature studies, analysis of laws and regulations, and secondary data related to cybercrime trends in Indonesia. The results indicate that the new Criminal Code has adopted a modern criminal justice system through a double-track system, but does not specifically regulate cybercrime, thus remaining dependent on Law Number 19 of 2016 concerning Electronic Information and Transactions. The effectiveness of criminal sanctions is deemed suboptimal due to limited law enforcement capacity, the complexity of cybercrime, and the imbalance between repressive and preventive approaches. Therefore, a more adaptive reconstruction of criminal sanctions is needed through the integration of technology-based repressive, rehabilitative, and restorative approaches. These findings emphasize the importance of comprehensive criminal law reform to increase the effectiveness of cybercrime prevention in the digital era.